PD-1/PD-L1 inhibitors in haematological malignancies: update 2017 - Jelinek, Tomas; Mihalyova, Jana; Kascak, Michal; Duras, Juraj; Hajek, Roman (Immunology, 2017)
The introduction of PD-1/PD-L1 pathway inhibitors is an important landmark in solid oncology with unprecedented practice-changing activity in various types of solid tumours. Among haematological malignancies, PD-1/PD-L1 inhibitors have been successful, so far, only in the treatment of classical Hodgkin lymphoma, which typically exhibits an over-expression of PD-1 ligands (PD-L1, PD-L2) due to alterations in chromosome 9p24.1. Such positive outcomes led to the US Food and Drug Administration approval of nivolumab use in relapsed Hodgkin lymphoma in 2016 as the first haematological indication. Although the results in other lymphoid malignancies have not been so striking, blockade of the PD-1/PD-L1 axis has led to meaningful responses in other lymphoma types such as diffuse large B-cell lymphoma, follicular lymphoma or several T-cell lymphomas. Monotherapy with PD-1/PD-L1 inhibitors in chronic lymphocytic leukaemia and multiple myeloma has been unsatisfactory, suggesting that a combinational approach with other synergistic drugs is needed. In the case of multiple myeloma, immunomodulatory agents together with corticosteroids represent the most promising combinations. Among myeloid malignancies, the anti-PD-1 monoclonal antibodies are examined dominantly in acute myeloid leukaemia and myelodysplastic syndromes in combination with potentially synergistic hypomethylating drugs such as 5-azacitidine, resulting in promising outcomes that warrant further investigation. We have described all available clinical results of PD-1/PD-L1 inhibitors in haematological malignancies and discussed related toxicities, as well as highlighted crucial preclinical studies in this review.
Keywords: signální transdukce; Signal Transduction; pembrolizumab; nivolumab; Humans; Hematologic Neoplasms; programmed death 1 receptor; Molecular Targeted Therapy; Antineoplastic Agents; antigeny CD279; výsledek terapie; lidé; zvířata; B7-H1 Antigen; hematologické nádory; medicína založená na důkazech; haematological malignancy; Treatment Outcome; klinické zkoušky jako téma; cílená molekulární terapie; protinádorové látky; Clinical Trials as Topic; Animals; antigeny CD274; Programmed Cell Death 1 Receptor; myeloma; Evidence-Based Medicine